Le processus de conversion politique d’un pasteur chaux-de-fonnier au cours de la Grande guerre : quand Jules Humbert-Droz devint un révolutionnaire suisse (1914-1919) - Clément Fontannaz (Les Cahiers de Framespa)
This article presents how biographical work helps understand the more global mechanisms of an individual’s political conversion. Here the purpose is to unravel the reasons which led a socialist pastor, who displayed no sign of any form of political radicalism at the outbreak of the First War, to turn to Bolshevism during the conflict. A political conversion that led to political, social, and friendly consequences. Jules Humbert Droz is no longer a mere socialist and anti-militarist militant, but becomes, in the eyes of the state, of moderate socialists, and of a section of the population, an agent of the Bolshevik subversion and an actor in the dissemination of revolutionary ideas in Switzerland. A political choice that allowed him to quickly climb the ranks of the international communist organizations and to become a revolutionary on an international scale.